Observation of Kinetic Alfven Waves and Mirror Mode Structure by THEMIS in Central Plasma Sheet - Guyer, Sinan; Can, Zehra (My University, 2015)
Substorms are effective indicator for many physical phenomena in magnetosphere. The central plasma sheet is the main research area in this study which is located in the nightside of the magnetosphere. Since plasma structure shows variability during the substorm, examination of the plasma changes can be observed. This variability contains low frequency structure and instability. The goal of the study is observation of this low frequency, namely kinetic Alfven wave structure and the mirror-mode structure which can be found in high beta plasma condition during substorm time. Charged particles can be accelarated by the KAWs because of their parallel electric field. The energization and acceleration mechanism can be driven by KAWs in central plasma sheet. Both these low frequency structures are important to understand of plasma responds during the substorm. Observations are made with THEMIS-E probe in tail-science, stage 23 of mission which provides a good opportunity for the researchers in order to investigate substorms.
Keywords: Magnetosphere; Substorm; Kinetic Alfven Wave; Plasma Instabilities; Mirror Mode Structure; Central Plasma Sheet; Instability